2007
DOI: 10.1038/sj.npp.1301348
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Transporter Gene (DAT1) Associated with Appetite Suppression to Methylphenidate in a Case–Control Study of Binge Eating Disorder

Abstract: Response to psychomotor stimulants is highly variable across individuals. Such inconsistencies are influenced by many factors including drug dose and polymorphic differences in genes that encode proteins, such as the dopamine transporter (DAT1), which are relevant to the site of action of these substances. The current study used a double blind, crossover (methylphenidate vs placebo) design to assess DAT1 genotype differences on appetite ratings to a snack-food cue in subjects with binge eating disorder (BED) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 40 publications
1
47
0
1
Order By: Relevance
“…[327] compared neural responses to food-reward outcomes in individuals with BN and with anorexia nervosa (AN), and found that individuals with BN had relatively greater activation in the dorsolateral prefrontal cortex, the insular cortex, and the pre-central gyrus. These studies compliment candidate genetic behavior investigations in BN that have reported altered allelic frequencies for the DAT gene [328] and DA receptor genes [329,330] in individuals with bulimia.…”
Section: Reviewsupporting
confidence: 74%
“…[327] compared neural responses to food-reward outcomes in individuals with BN and with anorexia nervosa (AN), and found that individuals with BN had relatively greater activation in the dorsolateral prefrontal cortex, the insular cortex, and the pre-central gyrus. These studies compliment candidate genetic behavior investigations in BN that have reported altered allelic frequencies for the DAT gene [328] and DA receptor genes [329,330] in individuals with bulimia.…”
Section: Reviewsupporting
confidence: 74%
“…Supporting Information Table S11 provides a synopsis of six different candidate gene studies in BED, which examined several different polymorphisms. [85][86][87][88][89][90] Two studies examined DSM-IV BED diagnoses in terms of the MC4R polymorphism and found no evidence that individuals with BED were any more likely to carry this polymorphism than non-BED subjects. 85,86 Similarly, Monteleone et al 87 examined the cDNA 385C polymorphism and failed to find evidence that this genetic abnormality is associated with BED, although it did appear to be associated with obesity.…”
Section: Supporting Informationmentioning
confidence: 99%
“…Pathologic overeating may be related to dysfunction of the dopamine (DA) and norepinephrine systems, as evidenced by genetic and pharmacologic findings and animal models. [20][21][22][23][24][25] Food stimulation generates abnormal DA responses in obese individuals, 26,27 and methylphenidate-mediated inhibition of DA transport leads to greater increases of DA levels within the caudate in obese individuals with BED compared with those without BED. 27 Agents, such as dextroamphetamine, that inhibit reuptake of DA and norepinephrine and elicit release of monoamine neurotransmitters 28 may alter pathologic BE and be feasible treatment options for BED.…”
mentioning
confidence: 99%